Sustainable strategies for disclosing environmental impact of the palm oil industry: a critical genre analysis - Osman, Hajibah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
The negative effects of global warming and stakeholders’ demand on the effects of business activities on the environment have resulted in the publication of sustainability reports. With sustainability reports from the palm oil industry and based on the Stakeholder Theory, this article examined the extent of disclosure on the environmental impact of this industry and the discourse to present the strategies taken to address the environmental impact of the business activities. The critical genre analysis conducted on the texts reveals the generic structure of the reports and the sustainable strategies. Starting with a promotional strategy by adding slogans to the titles and subheadings, the companies reinforce their strategies to address the negative environmental impact with facts and figures enhanced with effective visuals. These strategies are believed to convince the stakeholders that the companies have taken initiatives to mitigate the negative impacts of their businesses on the environment.